+0

# f(x) = x3 + 4x2 + x - 6, Which is the factored form of f(x)?

0
1422
9

f(x) = x3 + 4x2 + x - 6

Guest May 14, 2014

### Best Answer

#8
+19207
+5

1.) See "Vieta"

2.) You find $$x_1=1$$ do:

$$\begin{array}{ rlllr } ( x^3 & +4x^2 & +x & -6) & : (x-1) ={x^2}{+5x}{+6} \\ {{\underline{-( x^3}} & {\underline{-x^2)}}} & & & \\ 0 & +5x^2 & +x \\ & {\underline{-(5x^2}} & {\underline{-5x)}} \\ & 0 & +6x & -6 \\ && {\underline{-(6x}} & {\underline{-6)}} \\ && 0 & +0 \end{array}$$

\begin{array}{
rlllr
} (
x^3
&
+4x^2
&
+x
&
-6)
&
:
(x-1)
=\textcolor[rgb]{1,0,0}{x^2}\textcolor[rgb]{0,0,1}{+5x}\textcolor[rgb]{0,1,0}{+6}
\\
\textcolor[rgb]{1,0,0}{{\underline{-(
x^3}}
&
\textcolor[rgb]{1,0,0}{\underline{-x^2)}}}
&
&
&
\\
0
&
+5x^2
&
+x
\\
&
\textcolor[rgb]{0,0,1}{\underline{-(5x^2}}
&
\textcolor[rgb]{0,0,1}{\underline{-5x)}}
\\
&
0
&
+6x
&
-6
\\
&&
\textcolor[rgb]{0,1,0}{\underline{-(6x}}
&
\textcolor[rgb]{0,1,0}{\underline{-6)}}
\\
&&
0
&
+0
\end{array}

so we have: $$x^3+4x^2+x-6=(x-1)(x^2+5x+6)$$

x^3+4x^2+x-6=(x-1)(x^2+5x+6)

We solve:

$$\\x^2+5x+6=0\\ x^2+5x+({\frac{5}{2}})^2-({\frac{5}{2}})^2+6=0\\ \left( x+\frac{5}{2}\right)^2=\frac{25}{4}-6\\ \left( x+\frac{5}{2}\right)^2=\frac{1}{4}\qquad| \quad \pm\sqrt{}\\ x+\frac{5}{2}=\pm\sqrt{\frac{1}{4}}\\ x_{2,3}=-\frac{5}{2}\pm\frac{1}{2}\\ x_2=-\frac{5}{2}+\frac{1}{2}=-\frac{4}{2}=\underline{-2}\\ x_3=-\frac{5}{2}-\frac{1}{2}=-\frac{6}{2}=\underline{-3}\\$$

\\x^2+5x+6=0\\
x^2+5x+(\textcolor[rgb]{1,0,0}{\frac{5}{2}})^2-(\textcolor[rgb]{1,0,0}{\frac{5}{2}})^2+6=0\\
\left( x+\frac{5}{2}\right)^2=\frac{25}{4}-6\\
\left( x+\frac{5}{2}\right)^2=\frac{1}{4}\qquad| \quad \pm\sqrt{}\\
x+\frac{5}{2}=\pm\sqrt{\frac{1}{4}}\\
x_{2,3}=-\frac{5}{2}\pm\frac{1}{2}\\
x_2=-\frac{5}{2}+\frac{1}{2}=-\frac{4}{2}=\underline{-2}\\
x_3=-\frac{5}{2}-\frac{1}{2}=-\frac{6}{2}=\underline{-3}\\

$$\\x_1=1 \qquad x_2=-2 \qquad x_3=-3\\ \boxed{x^3+4x^2+x-6=(x-1)(x+2)(x+3)}$$

\\x_1=1 \qquad x_2=-2 \qquad x_3=-3\\
\boxed{x^3+4x^2+x-6=(x-1)(x+2)(x+3)}

heureka  May 15, 2014
Sort:

### 9+0 Answers

#1
+85675
0

This is all we can do......no further factoring available....!!!

CPhill  May 14, 2014
#2
+26626
+5

(x + 3)*(x - 1)*(x + 2) = x3 +4x2 + x - 6

To find this, start by assuming (x-a)*(x-b)*(x-c) =  x3 +4x2 + x - 6

The left-hand side can be expanded, to get: x3 - (a+b+c)*x2 +(a*b+a*c+b*c)*x -a*b*c =  x3 +4x2 + x - 6

By equating the coefficients of powers of x on both sides of this equation you get three simultaneous equations in a, b and c, which when solved, produce the result shown above.

By equating the coefficients I mean:

coeff of x2: -(a+b+c) = 4

coeff of x1: a*b + a*c +b*c = 1

coeff of x0: -a*b*c = -6

Alan  May 14, 2014
#3
+85675
0

Thanks, Alan...I haven't seen that one before....another tool for my chest !!

For some reason...this technique  - to my knowledge -isn't covered in Algebra in the States.....it should be!!

Thums Up from me !!

That's what I like about this site......something new to learn for evetyone!!!

CPhill  May 14, 2014
#4
+26626
0

Well, I should really add a warning here.  The method is not always very useful.  The danger is that, in general, by the time you do the various substitutions to isolate a, b or c, all you get is the original equation with x replaced by a, say!!

In this case it was fairly easy to guess that 1, 2 and 3 were involved, because their product had to be 6 (the other equations help determine the signs), and I started by assuming they would be integers (I reasoned the question probably wouldn't have been posed if they weren't).  Luckily, this reasoning panned out; however, in general it won't and one could guess forever without getting anywhere!

Alan  May 15, 2014
#5
+92206
0

Ok My turn

the roots have to be factors of 6 so I'd look at 1 first

f(1)=1+4+1-6=0 therefore (x-1) is a factor    [I am using factor theorem but it is just logical really]

I could now do algebraic division or synthetic division to find its cofactor but I'll just try easy possibilities first.

f(-2)=-8+16+-2-6=0 therefore (x+2) is another factor

(x-1)(x+2)=x2+x-2

$$(x^3+4x^2+x-6) \div (x^2+x-2) =x+3$$

I did the division but I don't know how to set it out in latex.  SO

$$(x^3+4x^2+x-6)=(x-1)(x+2)(x+3)$$

And that will work every time so long as the roots are integers.

Melody  May 15, 2014
#6
+19207
+5

1.) See "Vieta"

2.) You find $$x_1=1$$ do:

$$\begin{array}{ rlllr } ( x^3 & +4x^2 & +x & -6) & : (x-1) ={x^2}{+5x}{+6} \\ {{\underline{-( x^3}} & {\underline{-x^2)}}} & & & \\ 0 & +5x^2 & +x \\ & {\underline{-(5x^2}} & {\underline{-5x)}} \\ & 0 & +6x & -6 \\ && {\underline{-(6x}} & {\underline{-6)}} \\ && 0 & +0 \end{array}$$

so we have: $$x^3+4x^2+x-6=(x-1)(x^2+5x+6)$$

We solve:

$$\\x^2+5x+6=0\\ x^2+5x+({\frac{5}{2}})^2-({\frac{5}{2}})^2+6=0\\ \left( x+\frac{5}{2}\right)^2=\frac{25}{4}-6\\ \left( x+\frac{5}{2}\right)^2=\frac{1}{4}\qquad| \quad \pm\sqrt{}\\ x+\frac{5}{2}=\pm\sqrt{\frac{1}{4}}\\ x_{2,3}=-\frac{5}{2}\pm\frac{1}{2}\\ x_2=-\frac{5}{2}+\frac{1}{2}=-\frac{4}{2}=\underline{-2}\\ x_3=-\frac{5}{2}-\frac{1}{2}=-\frac{6}{2}=\underline{-3}\\$$

$$\\x_1=1 \qquad x_2=-2 \qquad x_3=-3\\ \boxed{x^3+4x^2+x-6=(x-1)(x+2)(x+3)}$$

heureka  May 15, 2014
#7
+92206
0

Hi Heureka,

Could you please post that latex here without it being in latex.  I just want to look at all the code, especially for the division bit.

I would have done it with the align function but I don't think that works in here.

I see you have used an array.  I have only used equarrays and again I don't think that they work in here

Thank you.

Melody  May 15, 2014
#8
+19207
+5
Best Answer

1.) See "Vieta"

2.) You find $$x_1=1$$ do:

$$\begin{array}{ rlllr } ( x^3 & +4x^2 & +x & -6) & : (x-1) ={x^2}{+5x}{+6} \\ {{\underline{-( x^3}} & {\underline{-x^2)}}} & & & \\ 0 & +5x^2 & +x \\ & {\underline{-(5x^2}} & {\underline{-5x)}} \\ & 0 & +6x & -6 \\ && {\underline{-(6x}} & {\underline{-6)}} \\ && 0 & +0 \end{array}$$

\begin{array}{
rlllr
} (
x^3
&
+4x^2
&
+x
&
-6)
&
:
(x-1)
=\textcolor[rgb]{1,0,0}{x^2}\textcolor[rgb]{0,0,1}{+5x}\textcolor[rgb]{0,1,0}{+6}
\\
\textcolor[rgb]{1,0,0}{{\underline{-(
x^3}}
&
\textcolor[rgb]{1,0,0}{\underline{-x^2)}}}
&
&
&
\\
0
&
+5x^2
&
+x
\\
&
\textcolor[rgb]{0,0,1}{\underline{-(5x^2}}
&
\textcolor[rgb]{0,0,1}{\underline{-5x)}}
\\
&
0
&
+6x
&
-6
\\
&&
\textcolor[rgb]{0,1,0}{\underline{-(6x}}
&
\textcolor[rgb]{0,1,0}{\underline{-6)}}
\\
&&
0
&
+0
\end{array}

so we have: $$x^3+4x^2+x-6=(x-1)(x^2+5x+6)$$

x^3+4x^2+x-6=(x-1)(x^2+5x+6)

We solve:

$$\\x^2+5x+6=0\\ x^2+5x+({\frac{5}{2}})^2-({\frac{5}{2}})^2+6=0\\ \left( x+\frac{5}{2}\right)^2=\frac{25}{4}-6\\ \left( x+\frac{5}{2}\right)^2=\frac{1}{4}\qquad| \quad \pm\sqrt{}\\ x+\frac{5}{2}=\pm\sqrt{\frac{1}{4}}\\ x_{2,3}=-\frac{5}{2}\pm\frac{1}{2}\\ x_2=-\frac{5}{2}+\frac{1}{2}=-\frac{4}{2}=\underline{-2}\\ x_3=-\frac{5}{2}-\frac{1}{2}=-\frac{6}{2}=\underline{-3}\\$$

\\x^2+5x+6=0\\
x^2+5x+(\textcolor[rgb]{1,0,0}{\frac{5}{2}})^2-(\textcolor[rgb]{1,0,0}{\frac{5}{2}})^2+6=0\\
\left( x+\frac{5}{2}\right)^2=\frac{25}{4}-6\\
\left( x+\frac{5}{2}\right)^2=\frac{1}{4}\qquad| \quad \pm\sqrt{}\\
x+\frac{5}{2}=\pm\sqrt{\frac{1}{4}}\\
x_{2,3}=-\frac{5}{2}\pm\frac{1}{2}\\
x_2=-\frac{5}{2}+\frac{1}{2}=-\frac{4}{2}=\underline{-2}\\
x_3=-\frac{5}{2}-\frac{1}{2}=-\frac{6}{2}=\underline{-3}\\

$$\\x_1=1 \qquad x_2=-2 \qquad x_3=-3\\ \boxed{x^3+4x^2+x-6=(x-1)(x+2)(x+3)}$$

\\x_1=1 \qquad x_2=-2 \qquad x_3=-3\\
\boxed{x^3+4x^2+x-6=(x-1)(x+2)(x+3)}

heureka  May 15, 2014
#9
+92206
0

Thank you Heureka

Melody  May 15, 2014

### 28 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details